INVESTIGATION OF PRESCHOOL: THE APPROACHES OF TEACHERS TOWARDS INCLUSION, INCLUSION COMPETENCIES AND CLASSROOM MANAGEMENT SKILLS: - Çobanoğlu, Necati; Demir, Selcuk (International Online Journal of Education and Teaching, 2023)
The aim of the study is to analyse the link between the approaches of preschool teachers towards inclusion, inclusion competencies as well as classroom management skills. The study is characterized by a correlational model. It was conducted with preschool teachers working in public schools selected by a simple random method in Malatya Province. 453 teachers participated in the study. The data were collected with Attitude Towards Inclusion Scale made by Loreman, Earle, Sharma and Forlin and adapted to Turkish by Cansız and Cansız, Teachers' Inclusion Competencies Scale made by Umesh Sharma, Tim Loreman and Chris Forlin and adapted to Turkish by Bayer, and also Classroom Management Competency Scale made by Elçiçek, Kinay and Oral. The collected data were evaluated with arithmetic average, Correlation Analysis and Structural Equation Modelling. At the end of the study, the approaches of preschool teachers towards inclusion, inclusion competencies and classroom management skills were found to be “Generally High”. The relationship between these variables were positive and medium. It was concluded the approaches of preschool teachers towards inclusion predicted their inclusion and classroom management competencies in a positive and significant way.